Implementation of Sharia Economic Principles on Duck Farming Business Performance in Pondokwaluh Hamlet - Vina Maulidatul Khasanah; Uliyatul Mu’awwanah (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the implementation of sharia economic principles on the performance of duck farming businesses in Pondokwaluh Hamlet. The purpose of this study is to examine the effect of the application of sharia economic principles on various aspects of duck farming business performance. The research method used is quantitative with a case study approach in Pondokwaluh Hamlet. Quantitative research method with case study research type, sampling with Non-probability sampling, research using certain techniques to select samples, this study uses Saturation Sampling, a sampling technique that uses all members of the population as samples. Data were analyzed using Statistical methods with SPSS (Statistical Product and Service Solutions) analysis software. The application of principles such as justice, honesty, prudence, and profit sharing systems have been shown to contribute to the sustainability and profitability of the business. However, obstacles to access to information, understanding, and limitations of sharia financial institutions need to be considered to optimize the positive impact of the application of these sharia economic principles. The results of the study are expected to contribute to the development of sustainable duck farming businesses and in accordance with sharia economic principles in Pondokwaluh Hamlet, as well as provide recommendations for policies that support improving the performance of sharia-based duck farming businesses.